2002
DOI: 10.1177/0011000002305001
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction

Abstract: Those who desire improvements in classroom learning must realize and acknowledge that school reform, especially when it focuses on disadvantaged students, cannot easily succeed if it ignores the circumstances of their out-of-school lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Although this self-reported interest and engagement in research collaboration was an encouraging finding, the actual publishing trends in key SC and CP journals were less promising. Our examination of JCP and TCP publication trends indicated a limited focus on school or SC concerns or topics, which is consistent with prior trends reported by Walsh & Galassi (2002) on the same journals. In fact, their review showed significant declines in both journals in K-12 school-related research for 1999-2000.…”
Section: Researchsupporting
confidence: 88%
“…Although this self-reported interest and engagement in research collaboration was an encouraging finding, the actual publishing trends in key SC and CP journals were less promising. Our examination of JCP and TCP publication trends indicated a limited focus on school or SC concerns or topics, which is consistent with prior trends reported by Walsh & Galassi (2002) on the same journals. In fact, their review showed significant declines in both journals in K-12 school-related research for 1999-2000.…”
Section: Researchsupporting
confidence: 88%